(untitled) (Comprehensive Journal of Science, 2025)
The study aimed to reduce risks in accounting information systems to enhance information security in e-commerce environments within commercial banks in Tripoli. It treated risk reduction as the independent variable and information security achievement as the dependent variable. A random sample of 142 was selected; 140 valid questionnaires were analyzed using SPSS (2 were excluded). Using a descriptive-analytical approach, the study found that the system has no major data quality issues, human error and intentional manipulation are not significant problems, and adequate input controls exist. Recommendations: Activate an intelligent automated system to monitor repeated/suspicious transactions Generate daily deviation reports Strengthen automated cross-auditing procedures